PSI-20 Effects of physical exercise on growth performance, and carcass and meat quality characteristics of Sunit sheep. (7th December 2018) - Su, R; Jin, Y; Luo, Y; Wang, B; Yuan, Q; Zhao, L; Su, L; Wang, D
Abstract: The objective of this study was to investigate the effects of muscle exercise on growth performance, proteins and genes expression, and carcass and meat quality characteristics of Sunit sheep. To this end, 24 Sunit sheep with same genetic background that were raised on extensive pasture for their first 9 months of life were randomly distributed into two groups (12 sheep each) and raised separately for 3 months until slaughter. The first group of sheep was kept on pasture and allowed to move freely outdoors (M Group), while the other group of sheep was kept in one pen inside the farm (control group or C Group). After slaughter, carcass characteristics were assessed and samples of the longissimus dorsi (LD) and biceps femoris (BF) muscles were taken to evaluate meat quality. Furthermore, the differences in the expression of muscle exercise-related proteins and genes between the two groups were analyzed by Western blotting and RT-PCR techniques. Results showed that growth traits, such as body length and height, and chest circumference and weight before slaughter were higher (P<0.01) in the M Group than in the C Group, while the lean and carcass yields were higher in C Group (P<0.05). A reduction of the pH1, pH24and colour a∗ and b∗ values was recorded in the LD muscle of the M sheep compared with C ones (P<0.01).These results may be associated with the greater (P<0.05) level of AMPK RNA expression, indicator of muscle glycolytic potential (GP), in the M group. The BF muscle of M sheep was tender (as assessed by shear force) than that of C sheep (P<0.01). In conclusion, allowing sheep a long-term exercise before slaughter can improve their growth rate, but at detriment of carcass yield.